Neddylation: A Versatile Pathway Takes on Chronic Liver Diseases - Yao, Jiping; Liang, Xue; Liu, Yanning; Zheng, Min (Frontiers in Medicine, 2020)
Neddylation is a ubiquitin-like posttranslational modification that conjugates neural precursor cell expressed developmentally downregulated-8 (Nedd8) to specific substrates for regulation of protein activity. In light of current researches, the neddylation pathway is aberrant in the pathogenesis of many diseases. In our review, we summarize the versatile roles of neddylation in chronic liver diseases (CLDs). CLDs are one of the leading causes of chronic disease-associated deaths worldwide. There are diverse etiologic agents causing CLDs, mainly including hepatitis B virus (HBV) infection, nonalcoholic fatty liver disease (NAFLD), chronic exposure to alcohol or drugs, and autoimmune causes. So far, however, there remains a paucity of effective therapeutic approach to CLDs. In this review, we summarized the role of the neddylation pathway which runs through the chronic hepatitis B/NAFLD–liver fibrosis–cirrhosis–hepatocellular carcinoma (HCC) axis, a canonical pattern in the process of CLD development and progression. The dysregulation of neddylation may provide a better understanding of CLD pathology and even a novel therapeutic strategy. Correspondingly, inhibiting neddylation via MLN4924, a small molecule compound targeting NEDD8-activating enzyme (NAE), can potently alleviate CLD progression and improve the outcome. On this basis, profiling and characterization of the neddylation pathway can provide new insights into the CLD pathology as well as novel therapeutic strategies, independently of the etiology of CLD.